PENGARUH MINAT BELAJAR DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS SMA NEGERI 1 PRAJEKAN KABUPATEN BONDOWOSO TAHUN AJARAN 2016/2017 - Kabela Putri; Sutrisno Djaja; Bambang Suyadi (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2017)
This study was conducted to determine the significant effect of learning interest and emotional intelligence on students achievement of class XI IPS SMAN 1 Prajekan Bondowoso in the 2016/2017academic year and to know the dominant variable between learning interest and emotional intelligence to students achievement class XI IPS SMAN 1 Prajekan Bondowoso in the 2016/2017academic year. The method of determining the location of research using the method of purposive area that is in SMAN 1 Prajekan Bondowoso. Determination of the number of respondents in this study using population method that is as many as 77 respondents. Data collection methods used consisted of methods: questionnaires, documents, and interviews. Data analysis used inferential / statistic is by using multiple regression analysis, regression line variance analysis, F test, regression line effectiveness, t test, and Standard Error Of Estimate. The results showed that there is a significant effect of learning interest and emotional intelligence on student achievement of class XI IPS SMAN 1 Prajekan Bondowoso District in the 2016/2017academic year which can be seen from the magnitude of F count = 184,364> F table = 3.12 with the level Significance F = 0,000 <a = 0.05. The amount of learning interest and emotional intelligence on students achievement class of 83.3%, the dominant variables affect student achievement is learning interest with a large percentage of 47.57% and emotional intelligence contributes 35.65%, while the remaining 16 , 7% are influenced by other independent variables that are not examined in this study.